Sistem Pakar Diagnosa Penyakit Skizofrenia Dengan Menerapkan Kombinasi Metode Constraint Satisfaction Problem (CSP) Dan Metode Certainty Factor - Lubis, Muhammad Khairi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Psychiatric illness is a change in mental function that causes disturbances in ways of thinking, will, emotions, actions and social relations that can cause obstacles in carrying out social roles. One type of psychiatric disorder that is very often known by the public is schizophrenia. If schizophrenia is not followed up, it will have a lot of impact on Indonesian society. For this reason, we need a system that is designed to mimic the expertise of an expert in answering questions and solving a problem in accordance with the knowledge of an expert that is entered into a computer system. The development of artificial intelligence technology that has occurred has enabled expert systems to be applied in detecting diseases using programming languages. One of them is in providing information about various problems, especially psychiatric disorders or often called schizophrenia. The expert system method used is a combination of the Constraint Satisfaction Problem (CSP) and Certainty Factor (CF) methods, which is one of the solutions that can display the final results of several diagnoses of schizophrenia. With the facilities provided to users, it is possible to use this system according to their individual needs. Users are given the convenience of finding information about the symptoms of Schizophrenia and its prevention. This expert system was created using the Microsoft Visual Basic 2010 application.